2018
DOI: 10.1155/2018/3074769
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Cells Exposed to Exogenous Palmitoleic Acid Either Adapt to Stress and Survive or Commit to Regulated Liponecrosis and Die

Abstract: A disturbed homeostasis of cellular lipids and the resulting lipotoxicity are considered to be key contributors to many human pathologies, including obesity, metabolic syndrome, type 2 diabetes, cardiovascular diseases, and cancer. The yeast Saccharomyces cerevisiae has been successfully used for uncovering molecular mechanisms through which impaired lipid metabolism causes lipotoxicity and elicits different forms of regulated cell death. Here, we discuss mechanisms of the “liponecrotic” mode of regulated cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 130 publications
1
19
0
Order By: Relevance
“…Altogether, the above findings and our previously published data [ 76 79 ] indicate that the efficiency of decreasing the risk of age-related liponecrotic RCD by LCA inversely correlates with the intracellular concentration of FFA. Thus, in support of our hypothesis proposed at the end of the previous section, LCA delays yeast chronological aging under CR conditions in part by decreasing the risk of liponecrotic RCD during PD and ST phases and actively increasing the chance of cell survival during these phases.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Altogether, the above findings and our previously published data [ 76 79 ] indicate that the efficiency of decreasing the risk of age-related liponecrotic RCD by LCA inversely correlates with the intracellular concentration of FFA. Thus, in support of our hypothesis proposed at the end of the previous section, LCA delays yeast chronological aging under CR conditions in part by decreasing the risk of liponecrotic RCD during PD and ST phases and actively increasing the chance of cell survival during these phases.…”
Section: Resultssupporting
confidence: 82%
“…We then examined if LCA influences the susceptibility of calorically restricted WT cells to liponecrotic RCD; this mode of age-related RCD can be triggered by a short-term treatment of yeast with FFA [ 36 , 76 79 ]. We found that in WT yeast cultured under CR conditions, LCA significantly increases clonogenic survival of cells briefly (for 2 h) treated with palmitoleic acid (POA; a monounsaturated form of FFA) if these cells were recovered during PD or ST phase of culturing (Figure 6C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In chronologically “old” yeast, the ethanol-dependent suppression of peroxisomal β-oxidation of fatty acids leads to the excessive accumulation of free (non-esterified) fatty acids (FFA) [ 3 , 21 , 37 ]. Such build-up of FFA accelerates yeast chronological aging by increasing the risk of an age-related mode of regulated cell death (RCD) called “liponecrosis” ( Figure 1 K) [ 3 , 98 , 99 , 100 ].…”
Section: Concentrations Of Some Metabolites Define the Rate Of Chrmentioning
confidence: 99%
“…The ethanol-driven excessive accumulation of unoxidized FFA in yeast peroxisomes (see Section 2.10 ) elicits several negative-feedback loops whose action causes a buildup of FFA and DAG in the ER and lipid droplets (LD) [ 3 , 100 , 101 ]. This buildup of FFA and DAG accelerates the onset of the liponecrotic mode of RCD, thereby increasing the risk of death and accelerating yeast chronological aging ( Figure 1 L) [ 3 , 21 , 98 , 99 , 100 ]. Thus, both FFA and DAG are pro-aging metabolites that shorten yeast CLS.…”
Section: Concentrations Of Some Metabolites Define the Rate Of Chrmentioning
confidence: 99%